INVESTIGATION OF MICROSTRUCTURAL AND MECHANICAL PROPERTIES OF ST-37 AND STRENX-960 STEELS BY A-TIG WELDING METHOD - İlyas Genç; Emre Kasım; Mehmet Fahri Saraç (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi)
The place of welding methods in-vehicle technologies is well established, significantly enhancing production speed and product quality. High toughness is crucial for welded metallic structures that require high strength and good processability. However, challenges such as reduced toughness and reliability in welds impact overall quality. This study focused on improving the weld seam quality of dissimilar metals, specifically St-37 and Strenx-960 steels, using the active tungsten inert gas (A-TIG) welding method with ZrO2 and Al2O3 fluxes. Experimental results showed that using ZrO2 flux yielded the highest mechanical performance, with a hardness of 494.8 HV, tensile strength of 1298 MPa, and impact energy of 113 J/cm². These findings highlight the superior adhesion and crystalline structure of ZrO2, which minimized defects in the weld seam and HAZ, ensuring consistency in mechanical properties. The study concludes that ZrO2 flux significantly enhances the mechanical integrity of welded joints, offering potential benefits for vehicle manufacturing.